Monitoring surface properties evolution of thermochemically modified cellulose nanofibres from banana pseudo-stem - Cordeiro, N. (2021)
The effect of steam explosion coupled with chemical treatment, on the surface properties of banana fibres obtained from the pseudo-stem of banana plant Musa sapientum was studied in detail by inverse gas chromatography (IGC). IGC experiments were performed in banana fibres from macro to nano stages at 293, 298 and 303 K. The analyzed fibres showed dispersive component of the surface energy between 39.59 and 48.03 mJ/m2, at 298 K. The interaction between the fibres and the high and low DN/AN* probes indicate the presence of both acidic and basic active sites on the fibres surface. The values of Ka and Kb suggest that predominantly basic active sites are involved in the specific adsorption process in the nanofi bres. During the thermochemical treatment, changes occur in the arrangement of macromolecular chains with the reduction of dispersive groups and the increase in some polar groups. This susceptibility of the surface to change its acid–base characteristics combined with a change in dispersive properties enhance the possibility of specific intermolecular interactions with different solvents, plasticizers, polymers or fillers, which is important to the practical applications of the nanofibres.